2015
DOI: 10.1111/os.12213
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Limb Shortening for Major Near and Complete Upper Extremity Amputations with Associated Neurovascular Injury: A Review of the Literature

Abstract: In the setting of near or complete upper extremity amputations with significant soft tissue loss and neurovascular compromise, upper extremity surgeons are faced with the challenge of limb salvage. There are a multitude of treatment options for managing skeletal and soft tissue injuries including provisional fixation, staged reconstruction, and an acute shortening osteotomy with primary rigid internal fixation. However, many complications are associated with these techniques. Complications of provisional fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 99 publications
0
13
0
1
Order By: Relevance
“…Diaphyseal humeral shortening, performed in conjunction with elbow disarticulation, can improve prosthetic fit and rotational control while preserving adequate space for the prosthesis. 9,10 Much the same way that a long-arm cast is difficult to keep on a child without a good supracondylar mold, prosthetic suspension can be particularly challenging in short residual limbs without a distal condylar flare. The benefit of retained humeral condyles can be simulated in long transhumeral amputees with an angulation osteotomy (humeral flexion osteotomy).…”
Section: Primary Amputationmentioning
confidence: 99%
“…Diaphyseal humeral shortening, performed in conjunction with elbow disarticulation, can improve prosthetic fit and rotational control while preserving adequate space for the prosthesis. 9,10 Much the same way that a long-arm cast is difficult to keep on a child without a good supracondylar mold, prosthetic suspension can be particularly challenging in short residual limbs without a distal condylar flare. The benefit of retained humeral condyles can be simulated in long transhumeral amputees with an angulation osteotomy (humeral flexion osteotomy).…”
Section: Primary Amputationmentioning
confidence: 99%
“…Few studies have reported the use of shortening osteotomies in the upper extremity for primary repair 17 and to facilitate nerve transfer without the need for an interpositional graft. 18-21 Lower extremity osteotomies for this purpose, however, have historically been avoided because of concern of functional limitations from leg length discrepancies. 17…”
Section: Discussionmentioning
confidence: 99%
“…Acute shortening and fusion can be achieved provided the bone defect is <2-3 cm [7] . Greater shortening increases the risk of vascular compromise due to vessel kinking [8] and alters tendon excursion leading to flexor/extensor imbalance and reduced active range of motion. In this case, as vascular reconstruction was required, vessel kinking was less of a concern.…”
Section: Discussionmentioning
confidence: 99%